Effect of Plant Hormones on the Production of Biomass and Lipid Extraction for Biodiesel Production from Microalgae Chlorella Sp. - Bhuyar, P.; M. M., Yusoff; Mohd Hasbi, Ab. Rahim; Sundararaju, Sathyavathi; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (Faculty of Biotechnology and Food Sciences, 2019)
The economic globalization and rapid energy depletion require alternative forms of energy which is more reliable, sustainable and renewable without causing adverse effects to the life forms. Microalgae are currently considered to be one of the most promising alternative sources for biodiesel and the application of phytohormones has also been considered a promising way to increase the production of lipid from microalgae recently. The present study is aimed to cultivate the algal species, Chlorella as a feedstock and the effect of various concentrations of phytohormones such as 6-Benzylaminopurine (BAP), Gamborg’s b-5 vitamins, Indole-3-butyric acid (IBA), 2, 4-Dichlorophenoxyacetic acid (2,4-D) was used for the production of lipid. The extracted lipid oils were then converted into methyl ester via the transesterification process. Indole-3-butyric acid (IBA) relatively supported the maximum growth of 7.185 g/ ml and the lipid yield was 3.5g/ml. The GC-MS characterization showed many peaks corresponding to the fatty acid methyl esters. Among those Ethylbenzene, o-Xylene, Benzene,1,2,4-trimethyl and Decane peaks of hydrocarbons were found important in the biofuel production. The current study demonstrates that the phytohormone IBA accelerate the microalgae growth and also induce the production of lipid oils for biodiesel production.